Analysis Value Engineering at Work Apartment Building Wall - Salsabila, Arna; Setyowulan, Desy; Arifi, Eva (ASTONJADRO, 2024)
It was Optimizing resources to analyze cost efficiency in implementing construction projects. One method that can be used for resource optimization is value engineering (VE). Value engineering (VE) as a management technique to determine the efficiency between the cost and performance of a product or project and stay on appearance, quality and maintenance. Then value engineering is applied to the construction of apartment buildings to get cost efficiencies from the initial budget planning. This study aims to determine the effectiveness of value engineering in the construction of apartment buildings, especially in-wall installations. The VE method consists of five stages: Information stage, the creativity stage, the analysis stage, the development stage, and the presentation stage. Information stage, data collection in the form of cost planning, detail engineering design, work plan and terms. Based on the data obtained, the total contract value for the apartment building is Rp. 87,328,000,000. wall installation as one of the highest cost contributors. There are two alternative recommendations, namely sandwich panel walls and precast walls. The analysis found that the sandwich panel wall has the most efficient value, namely the total RAB value of 2.5% from the initial plan.